Rebuilding the fire and rescue services : policy delivery and assurance - Murphy, Peter; Lakoma, Katarzyna; Eckersley, Peter; Glennon, Russ (Bingley, U.K. : Emerald Publishing Limited, 2020)
Contemporary reforms of the fire and rescue service result from two excoriating reports from the National Audit Office and the Public Accounts Committee that demonstrated the inadequacy of contemporary policy, service delivery and public assurance for fire and rescue services in England. This book focuses on the key reforms proposed by Theresa May when she was Home Secretary in response to these reports and critically examines the new National Framework and the new external Inspectorate that were created as a result. Rebuilding the Fire and Rescue Services will prove invaluable for both academics and practitioners in order to build a more efficient and effective performance regime for this essential emergency service. It demonstrates the context, the parameters, the agencies and the inter-relationships that operate within the areas of policy development, service delivery and public assurance in the service. It shows how the new national framework and the new inspectorate can be improved. Most of all it shows the need for robust data and intelligence at both the national and local levels.
Chapter 1: Alarm bells ringing: introduction -- Chapter 2: The gold standard: an evaluative model -- Chapter 3: A sinking platform: the data dilemma -- Chapter 4: Two steps forward and one back: the 2018 national framework -- Chapter 5: So near and yet so far: a rigorous and independent inspectorate? -- Chapter 6: A glass half-full or a glass half-empty: conclusions, reflections and reactions.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Emergency management -- Law and legislation -- England; First responders -- England; Fire departments -- England; Political Science -- Public Policy -- General; Fire services